Fabrications of cellulose nanocomposite for tailor-made applications. Issue 6 (July 2021) - Ismail, Muhamad Fareez; Jasni, Ainil Hawa; Ooi, Der Jiun
The unique properties of nanocelluloses (NCs), including nanodimension, renewability, low toxicity, biocompatibility, biodegradability, easy availability, and low cost, render them the ideal nanomaterials for diverse applications. Composite material consists of matrix material with low volume fraction and self-assembled NC fibers with a high volume fraction of reinforcing domain. These two-phase components are often combined to promote stiffness and improve toughness (by dissipating materials fracture energy). The challenge, however, is to control the alignment and distribution of NC within the matrix. Recent research has been focusing on the production of composites using different methodologies such as electrospun cellulose nanofibers, polymer-grafted NC, nanoparticle binding on NCs, assembly of NCs at the air/water and oil/water interfaces, protein-mediated interactions on NCs, and atomic layer deposition on NCs. In this case, NC serves as an appropriate candidate for composites preparation in comparison to the non-biodegradable nanofillers (e.g. carbon nanoclay and nanotube).